The prevalence and associated factors of the minimum acceptable diet among children aged 6-23 months in Ethiopia: A community-based cross-sectional study. - Girma Cheru Bikila; Godana Arero; Sultan Kalu; Kedir Teji Roba; Tesfaye Getachew Charkos (PLoS ONE)
Background A minimum acceptable diet for children aged 6-23 months is limited globally, with Ethiopia's proportion reducing to one in nine. This study was aimed to assess the prevalence of the minimum acceptable diet and associated factors among children aged 6-23 months in Dera town, Oromia, Ethiopia. Methods A community-based cross-sectional study was conducted. Systematic random sampling techniques were used to select the study subjects. The data was coded, entered into Epi-Info version 7, and then exported to SPSS version 24 for analysis. The variance inflation factor and tolerance test are used to check multicollinearity. Descriptive statistics of frequency (%) were used. Hosmer and Lemeshow's goodness-of-fit test at a P-value > 0.05 is considered the model fit. Bivariate and multivariate logistic regression analyses were computed with a 95% confidence interval, and a P-value < 0.05 was, considered statistically significant. Results A total of 430 study subjects were included in this study. The prevalence of a minimum acceptable diet was 36.5% (95% confidence interval (CI): 32, 41%). In the adjusted model, mothers attaining a primary school (adjusted odds ratio (AOR) = 2.7, 95%CI: 1.3, 4.8), college and above education (AOR = 4.3, 95%CI: 1.4, 13), child age between 12-17 months (AOR = 6.2, 95%CI: 2.80, 13.50) and 18-23 months (AOR = 4.61, 95%CI: 2.04, 10.40), ANC visit four or more (AOR = 2.0, 95%CI: 1.2, 3.4), and not feeding breast (AOR = 0.15, 95% CI: 0.07, 0.31) were significantly associated with meeting the minimum acceptable diet. Conclusion This study showed that the practice of a minimum acceptable diet was low, according to the World Food Program target. Mothers' educational status, antenatal care visits, age of the child, and breastfeeding were the predictors of the minimum acceptable diet.